Variations in pH significantly affect cadmium uptake in grafted muskmelon (Cucumis melo L.) plants and drive the diversity of bacterial communities in a seedling substrate - Zhang, Jian (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.